Partial pathogenicity chromosomes in Fusarium oxysporum are sufficient to cause disease and can be horizontally transferred. (14th June 2020) - Li, Jiming; Fokkens, Like; Conneely, Lee James; Rep, Martijn
Summary: In Fusarium oxysporum f.sp. lycopersici, all effector genes reported so far – also called SIX genes – are located on a single accessory chromosome which is required for pathogenicity and can also be horizontally transferred to another strain. To narrow down the minimal region required for virulence, we selected partial pathogenicity chromosome deletion strains by fluorescence‐assisted cell sorting of a strain in which the two arms of the pathogenicity chromosome were labelled with GFP and RFP respectively. By testing the virulence of these deletion mutants, we show that the complete long arm and part of the short arm of the pathogenicity chromosome are not required for virulence. In addition, we demonstrate that smaller versions of the pathogenicity chromosome can also be transferred to a non‐pathogenic strain and they are sufficient to turn the non‐pathogen into a pathogen. Surprisingly, originally non‐pathogenic strains that had received a smaller version of the pathogenicity chromosome were much more aggressive than recipients with a complete pathogenicity chromosome. Whole genome sequencing analysis revealed that partial deletions of the pathogenicity chromosome occurred mainly close to repeats, and that spontaneous duplication of sequences in accessory regions is frequent both in chromosome deletion strains and in horizontal transfer strains.